GADGET DALAM BERKARYA SENI GRAFIS - Johan Sentosa; Yofita Sandra; Budiwirman Budiwirman (Serupa The Journal of Art Education, 2020)
Communication technology in the form of gadgets in the most unique phenomenon in this day, it is because not a few users tend to take advantage a moment of being together using this technology. The gadget in this artworks aims to visualize the effect of its use in everyday life, through the serigraphy technique in the creating process as one of the choices in making graphic artworks. After various observations and long steps to work, 10 artworks were created and displayed, they are : 1) Moment, 2) Blood and Flesh, 3) Jail, 4) Hoax, 5) New Toys, 6) Mastered, 7) Light in Darkness, 8) A Spy, 9) Blind, 10) Easy But Complicated. These are the result in the gadget influence artworks that become a picture of revealed behavior in life, besides these graphic artworks are expected to be a source of encouragement for other creators.Keyword: Gadget Influence, Serigraphy